Short communication: Study on veterinarian communication skills preferred and perceived by dairy farmers. (April 2015) - Cipolla, M.; Zecconi, A.
Highlights: We investigated veterinarian and other consultants' communication skills. Communication skills were significantly lower than desired ones for all consultants. Among consultants, veterinarians were the most appreciated and skilled consultants. Abstract: Effective communication in dairy farms improves management and herd health, and it is also pivotal for public health in a "from farm to fork" perspective. This paper reports the results of a descriptive study on dairy farmers' perception of veterinarian and other consultants' communication skills. Perceived communication skills showed to be significantly lower than desired ones for all the professional figures considered. Despite these unsatisfactory results, veterinarian were the most appreciated and skilled consultants. The observed farmers' dissatisfaction increases farmers' difficulties in identifying proper targets and proper consultant. An increase in the skill of veterinarian to deliver effective and tailored messages could help to overcome the problem.